Communication Strategies Between Teachers and Parents on Students’ English Proficiency - Aulia Amalina Putri; Sri Kusuma Ningsih (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
This study examines how teachers and parents use communication strategies to help middle school students improve their English language skills. A qualitative approach involving semi-structured interviews with five parents and five English teachers was employed, based on Epstein’s framework of parenting, communicating, volunteering, learning at home, decision-making, and collaborating with the community. The findings reveal that teachers and parents generally communicate effectively using WhatsApp and phone calls, but there are areas that need improvement. Parents participation in volunteering and decision-making activities is infrequent, and the school lacks collaboration with external communities. Despite these limitations, both teachers and parents recognize the importance of their communication in supporting students' English language proficiency. The study highlights the need for more comprehensive parental involvement strategies to enhance students' academic achievement.